Identity of the Courtyard in Traditional and Contemporary Erbil City Houses - Rawaz Abdullah; Aisha Saied; Dlman Azeez (Eurasian Journal of Science and Engineering)
The most significant element of architectural design across various cultures is our courtyard; the ongoing debate in contemporary architectural design is identity. It acknowledges the role of space as the most important standard to measure the human identity of a building is shaped by specific climate, place, and time. The problem articulates within human thoughts and technological progression; this evolving courtyard is an opportunity for exploration and redefinition of courtyards, depending on social and cultural changes among the Kurdish people. The research focus and purpose are well defined and centered around comparing the courtyard identity in both traditional and contemporary Kurdish houses to understand the factors influencing courtyard identity by including comfort, privacy level, and aesthetics to achieve a sophisticated understanding of human necessities in the context of courtyard design. This study resulted from comprehensive prior studies. The survey involves a group of questionnaires designed to gather specific information from designers about courtyard design in traditional and contemporary houses. This study highlights the significant differences between courtyard designs in Kurdish towns and urban houses. In traditional homes, courtyards play a crucial role in ensuring privacy, comfort, and functionality, shaped by human behavior and influenced by religious and cultural norms. These spaces are designed with flexibility, catering to a variety of household needs. In contrast, courtyards in contemporary urban homes are often designed with a focus on aesthetics, losing much of the functional and cultural significance found in their traditional counterparts.